Analysis Of Interest in Using Special Bus Transportation in Kuta as A Solution to Overcome Congestion Due to Vehicle Volume Exceeding Road Capacity - Mardikawati, Budi; Suartawan, Putu Eka (Journal of Information System, Technology and Engineering, 2024)
Traffic congestion in Kuta, Bali, is getting worse as the number of vehicles increases beyond the road capacity. Although various traffic engineering management efforts have been made, the congestion problem has not been resolved effectively. This study aims to analyze public interest in using special bus transportation as an alternative transportation to reduce congestion in Kuta. The stated preference survey method was used to collect data from respondents who are road users in the Kuta area. The results of the study showed that there was public interest in using special bus transportation, which was 83.3% (or 375 out of 450 respondents), especially among tourists. Factors such as comfort, environmental friendliness, and more affordable fares were the main considerations for respondents. With adequate support from the government and transportation service providers, this special bus transportation has the potential to be an effective solution to reduce congestion in Kuta. This study recommends the implementation of a trial of special bus services on busy routes and integration with other public transportation systems.